Diversity of green infrastructure network and cognitive well-being of urban residents - Mansor, Mazlina; Said, Ismail (Ministry of Housing and Local Government Malaysia., 2009)
This paper presents a preliminary study on the roles of green infrastructure network as social spaces for well-being of urban residents.